Public services as fundamental rights - Matias-Camargo, Sergio Roberto (Universidad Pedagógica y Tecnológica de Colombia, 2014)
It deals with public services as fundamental rights. It applies a social, legal and interdisciplinary approach, that overcomes the formalism and positivist reductionism that is restricted to written rules and “what they say”. It examines public services as a gender, putting emphasis on the essential ones and treating elements for reconsidering their theory and practice, their constitutional and legal enshrinement and their formal and material guarantees.